Effect of methylprednisolone on perivascular pulmonary edema, inflammatory infiltrate, VEGF and TGF-beta immunoexpression in the remaining lungs of rats after left pneumonectomy - Guimarães-Fernandes,F. (2011)
Pneumonectomy is associated with high rates of morbimortality, with postpneumonectomy pulmonary edema being one of the leading causes. An intrinsic inflammatory process following the operation has been considered in its physiopathology. The use of corticosteroids is related to prevention of this edema, but no experimental data are available to support this hypothesis. We evaluated the effect of methylprednisolone on the remaining lungs of rats submitted to left pneumonectomy concerning edema and inflammatory markers. Forty male Wistar rats weighing 300 g underwent left pneumonectomy and were randomized to receive corticosteroids or not. Methylprednisolone at a dose of 10 mg/kg was given before the surgery. After recovery, the animals were sacrificed at 48 and 72 h, when the pO2/FiO2 ratio was determined. Right lung perivascular edema was measured by the index between perivascular and vascular area and neutrophil density by manual count. Tissue expression of vascular endothelial growth factor (VEGF) and transforming growth factor-beta (TGF-β) were evaluated by immunohistochemistry light microscopy. There was perivascular edema formation after 72 h in both groups (P = 0.0031). No difference was observed between operated animals that received corticosteroids and those that did not concerning the pO2/FiO2 ratio, neutrophil density or TGF-β expression. The tissue expression of VEGF was elevated in the animals that received methylprednisolone both 48 and 72 h after surgery (P = 0.0243). Methylprednisolone was unable to enhance gas exchange and avoid an inflammatory infiltrate and TGF-β expression also showed that the inflammatory process was not correlated with pulmonary edema formation. However, the overexpression of VEGF in this group showed that methylprednisolone is related to this elevation.